From Spanish fury to good football: the origins of "tiki-taka" - García-Martí, Carlos (Política y Sociedad, 2018)
National playing styles help create national identities within the countries, especially concerning the most popular sports. In Spain, this football national style has gone from the Spanish fury to the tiquitaca. Up to now, the analysis that have been carried out on this process have focused on media discourses as reproducing the hegemonic social consensus. This study aims to extend the field of study to the practices of professional athletes and their identities and shared culture. Thus, through 31 in-depth interviews with former elite football players and coaches, along with journalists and referees, the Spanish football discourse transformation in the early 1990s is reconstructed, linking it to the ongoing commodification process in professional football. At the same time, it is clear that this discourse change involved at the same time a deep modification of the training and playing practices, and that both practices and discourses fed each other to modify the hegemonic understanding of football in Spain.